Accurate and non-invasive localization of multi-focal ground-glass opacities via electromagnetic navigation bronchoscopy assisting video-assisted thoracoscopic surgery: a single-center study - Zeng, Chenxi; Yang, Guang; Wei, Lu; Wang, Junhui; Wang, Xue; Ye, Fan; Fu, Xiangning; Cai, Yixin; Wang, Jianing (Frontiers in Oncology, 2023)
Abstract： Background: Accurate localization of multi-focal ground glass opacities (GGOs) is crucial for successful video-assisted thoracoscopic surgery. Electromagnetic navigation bronchoscopy (ENB) provides a minimally invasive and dependable approach for precise localization. This study assessed the accuracy and safety of ENB-guided localization in cases involving multi-focal GGOs. Methods: This retrospective study presents a single-center investigation into ENB-guided localization, utilizing methylene blue, for multifocal ground glass opacities (GGOs) assisting video-assisted thoracoscopic surgery (VATS). Clinical, surgical, and pathological data were collected from patients who underwent ENB-guided localization between December 23, 2019, and August 31, 2022. Results: The study examined 57 patients with multifocal GGOs who underwent ENB-guided localization and VATS. A total of 150 GGOs were treated, with ENB-guided localization taking a median time of 120 minutes. Following localization, all patients proceeded to VATS, with a median duration of 170 minutes. The median lesion size measured 7.8mm, with a 5mm distance between GGO and pleura or fissure. When the distance between GGO and pleura/fissure exceeded 1cm, an additional location point was introduced below the pleura or fissure based on GGO location. No complications related to localization were observed. The overall malignancy rate stood at 66%. Location precision was confirmed by measuring the marker-to-GGO lesion distance, resulting in a 94% (141/150) accuracy rate for GGO localization. Conclusion: ENB-guided methylene blue injection is a safe and precise method to treat multifocal GGOs, potentially minimizing operation time and simplifying lesion detection.